Birokrasi Pemerintahan Pendekatan Sistem Hukum Moral dan Manajemen dalam Upaya Pencegahan Korupsi di Indonesia - Saepudin, Eli Apud; Laksana, April; Wahyiah, Ita Rosita (ANTASENA: Governance and Innovation Journal, 2023)
The bureaucracy has full authority in the management of government budgets and the delivery of public services. Bureaucratic power can lead to abuse of power and corruption in government activities. Lord Epton sad "power tends to corrupt, absolute power corrupts absolutely". The statement illustrates that government power has the opportunity to become corrupt. Corruption is the most serious problem not only in developing countries but also in developed countries. There are many strategies to fight it. Corruption has been successfully proven by experts and practitioners around the world. Today, there are three main approaches to fighting corruption. First, the legal approach that emphasizes the development of national laws through political decisions and emphasizes law enforcement that upholds the laws of the country. Second, the moral approach, which emphasizes efforts to persuade people not to do wrong and avoid abuse of power with self-awareness. Third, the management system approach emphasizes the development of a management system based on transparency and accountability. The third approach aims to eliminate opportunities for corruption by designing a management system that does not provide opportunities for government officials to commit corruption by providing space for the public to control all government activities through investigation and claim mechanisms. The first approach has weaknesses